Crystal Engineering Strategies for Tailoring Mechanical Properties of Structural Materials - Neha Sahu; Rizwan Arif (International Journal of Crystalline Materials, 2024)
Crystal engineering has emerged as a promising approach for designing materials with tailored mechanical properties, enabling advancements in various fields such as aerospace, automotive, and construction. This review examines the diverse strategies employed in crystal engineering to manipulate the mechanical behavior of structural materials. One key strategy involves controlling the crystal structure at the atomic level through techniques such as alloying, doping, and phase transformations. Alloying introduces foreign atoms into the crystal lattice, altering its mechanical properties by influencing factors such as strength, ductility, and corrosion resistance. Doping, on the other hand, involves intentional substitution of atoms within the crystal lattice to enhance specific mechanical characteristics. Furthermore, the manipulation of grain boundaries and defects within crystalline materials offers another avenue for tailoring mechanical properties. Grain boundary engineering techniques enable the optimization of grain size and orientation to enhance strength, toughness, and fatigue resistance. Additionally, the deliberate introduction of defects, such as dislocations and vacancies, can significantly influence mechanical behavior by affecting deformation mechanisms and stress distribution. Nanostructuring represents a cutting-edge approach in crystal engineering, wherein materials are engineered at the nanoscale to impart unique mechanical properties. Nanomaterials exhibit superior strength-to-weight ratios and enhanced mechanical robustness due to their high surface area-to-volume ratio and unique deformation mechanisms. Moreover, advances in computational modeling and simulation techniques have greatly facilitated the design and optimization of crystal structures for specific mechanical properties. Molecular dynamics simulations and density functional theory calculations provide valuable insights into the atomic-scale mechanisms governing material behavior, guiding the rational design of novel structural materials. In conclusion, crystal engineering offers a versatile toolkit for tailoring the mechanical properties of structural materials, enabling the development of high-performance materials with tailored properties for diverse applications. By harnessing the synergistic combination of experimental techniques, computational modeling, and theoretical insights, researchers can continue to push the boundaries of material design and unlock new possibilities for engineering innovative materials with unprecedented mechanical performance.
Keywords: Alloying; Crystal engineering; Grain boundary engineering; Mechanical properties; Nanostructuring